Investigation of shelf life of strawberry from Cameron Highlands through gamma irradiation / Mohd Zulfadli Adenan, Siti Hasanah Mhd Hambali - Adenan, Mohd Zulfadli; Mhd Hambali, Siti Hasanah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
This study was an experimental study to investigate the shelf life extension of strawberry from Cameron Highlands through the different exposure doses of gamma irradiation. The strawberries were divided into four groups. Each group was irradiated by gamma irradiation and had their own specific gamma dose. The strawberries were divided into four groups by labelling A - 0.0 kGy (controlled) B1 - 0.4 kGy, B2 - 0.8 kGy and B3 - 1.2 kGy. The shelf life group calculated the weight loss and the decay rate of the strawberries from samples A, B1, B2, and B3. Findings from the percentage of weight loss showed that there was no consistency in weight loss to the differences in irradiation dose of the strawberry. From the findings of the decay rate, it can be concluded that the higher the dose of irradiation, the lower the time taken for the strawberries to decay.